Sampling planning of micronutrients and aluminium of the soils of São Paulo, Brazil - Marques Jr., José [UNESP]; Alleoni, Luis Reynaldo Ferracciú; Teixeira, Daniel De Bortoli [UNESP]; Siqueira, Diego Silva [UNESP]; Pereira, Gener Tadeu [UNESP] (Elsevier, 2015)
Spatial distribution of micronutrients and aluminum of the soils varies widely in space and time under the influence of natural and anthropogenic factors. Fulfilling sustainable production requirements requires precisely characterizing micronutrients and aluminium variability in order to implement effective agronomical practices. The aim of this work was to propose a sample planning for available micronutrients and aluminium in soils from the Brazilian state of Sao Paulo, at the state scale. To this end, a total of 19,360 soil samples from 311 municipalities across the state were analysed for available Cu, Fe, Mn, Zn and B and for toxic Al. Variability in their concentrations was assessed by using descriptive statistics and geostatistics. Micronutrients in soils varied markedly across the state (coefficient of variation - CV > 77%), with geostatistical ranges from 189 km for Zn to 589 km for Mn and 394 km for standardized variogram. Based on the results, the minimum number of sampling points needed to describe micronutrients and aluminium, at state scale, in soils varied from 179 to 1743 as estimated from the individual variographic range. The standardized variogram indicates the needs to be 400 samples. Our results indicate that in future mapping studies, to characterize the micronutrients and aluminium of São Paulo at a state scale more detailed than the first one, it is necessary to use a sampling density for each geomorphological region with a spacing less than 33 km (Coastal province), 29 km (Western Plateau), 22 km (Cuestas basálticas) and 21 km (Peripheral depression and Atlantic plateau). We believe these sample spacing can be used in other places with the same landscape forms and geology (geomorphological compartments).
Keywords: Geostatistics; Ordinary kriging; Sampling plans; Standardized variogram